Search for long-lived particles decaying into muon pairs in proton-proton collisions at √s = 13 TeV collected with a dedicated high-rate data stream - KAYA, MİTHAT (My University, 2022)
© 2022, The Author(s).A search for long-lived particles decaying into muon pairs is performed using proton-proton collisions at a center-of-mass energy of 13 TeV, collected by the CMS experiment at the LHC in 2017 and 2018, corresponding to an integrated luminosity of 101 fb−1. The data sets used in this search were collected with a dedicated dimuon trigger stream with low transverse momentum thresholds, recorded at high rate by retaining a reduced amount of information, in order to explore otherwise inaccessible phase space at low dimuon mass and nonzero displacement from the primary interaction vertex. No significant excess of events beyond the standard model expectation is found. Upper limits on branching fractions at 95% confidence level are set on a wide range of mass and lifetime hypotheses in beyond the standard model frameworks with the Higgs boson decaying into a pair of long-lived dark photons, or with a long-lived scalar resonance arising from a decay of a b hadron. The limits are the most stringent to date for substantial regions of the parameter space. These results can be also used to constrain models of displaced dimuons that are not explicitly considered in this paper. [Figure not available: see fulltext.].
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; Beyond Standard Model; Dark Matter; Hadron-Hadron Scattering; Beyond Standard Model; Dark Matter; Hadron-Hadron Scattering